Implementation of Curriculum Management at Private Madrasah Education Institutions - Hilma Rofi Mahfudzhah; Emmanuel Eyo (Jurnal Pendidikan Nusantara, 2023)
The curriculum is essentially a component content that is crucial in the educational environment. Curriculum management is a measure of the success and quality of an educational institution in the implementation of learning activities. Therefore, the author aims to analyse the problematic curriculum as well as how the curriculum development strategy is used in madrasas. This article uses a qualitative method with a pattern of interviews and observations to collect information which is then reviewed by the literature study method.  The results of this mini research are: 1) Madrasah Tsanawiyah (MTs) Muhammadiyah 2 Jenangan Ponorogo experiences several problems in implementing the new curriculum, so good management is needed to support the implementation of the curriculum in accordance with the curriculum objectives. 2) The final result in the implementation of the curriculum in this madrasa, the institution has several strategies to support the implementation of the new curriculum with a project-based work programme, so that students can freely express themselves while honing their skills to live the values contained in the new curriculum. 3) One form of curriculum strategy evaluation is by utilising Information Technology (IT) as an infrastructure tool that supports the performance of teachers and students in learning and learning activities, so that the use of IT can be collaborated with other strategies.  In addition, the implementation of the curriculum also requires the cooperation of all school members as well as parents of students.